Innovations in Neurostimulation Therapies for Chronic Pain Management (Review Journal of Neurological & Medical Sciences Review, 2023)
Chronic pain is a significant healthcare challenge affecting millions worldwide,  often resistant to conventional treatments. Neurostimulation therapies have emerged as promising  alternatives, offering relief to patients with various chronic pain conditions. This article reviews  recent innovations in neurostimulation techniques, including spinal cord stimulation, peripheral  nerve stimulation, and deep brain stimulation, highlighting their mechanisms of action, efficacy,  and potential applications. The discussion also explores advancements such as closed-loop systems  and non-invasive modalities, assessing their impact on improving pain management outcomes.  Through a comprehensive analysis of current research and clinical trials, this paper underscores the evolving landscape of neurostimulation therapies and their role in addressing the complex nature  of chronic pain. Keywords: Chronic pain, Neurostimulation, Spinal cord stimulation, Peripheral nerve stimulation, Deep  brain stimulation, Pain management, Innovation.